Zgoda małżonków w procesie skróconym przed biskupem - Gałkowski, Tomasz (Ius Matrimoniale, 2019)
The study analyzes the answer of the Pontifical Council for Legislative Texts regarding the need to obtain the explicit consent of the other party as a sine qua non condition for the commencement of the Briefer Matrimonial Process before the Bishop. The author analyzes the rations for formulating the content of the answer, but also points to situations that impede obtaining such a consent. He points out that the actual grounds for the annulment of a marriage should prevail over the formal reason.